A retrospective review: The outcomes of patients with anal carcinoma receiving treatment at Groote Schuur Hospital - Dalmeyer, Lisa (Division of Radiology, 2017)
Objectives: The objective of this study was to compare the outcome of two cohorts of patients with anal squamous carcinoma treated with split course chemoradiation as opposed to continuous chemoradiation at Groote Schuur Hospital. Demographics including age at diagnosis, gender and HIV status were reviewed. The stage at diagnosis, the acute treatment toxicities and all surgical procedures were noted. The outcomes included complete response rate, local control rate, loco-regional failure free survival, colostomy-free survival and overall survival. Design and Methods: The data was obtained from patient records of all patients with histologically conﬁrmed anal squamous cell carcinoma seen and registered at the Department of Radiation Oncology at Groote Schuur Hospital. Patients included were those treated with radical intent that presented between the years of 2008 and 2012. This data was then compared with a similar study performed between 2000-2 004-. Results: A total of 72 patients diagnosed with anal squamous carcinoma were seen at Groote Schuur Hospital in the 5-year period, of which 4-0 patients ﬁtted the criteria for this study. The median age was 53 years, with a slight male preponderance (55%) and 27.5% tested HIV positive. A total of 68% of patients had T3 and T4- disease, with 4-2.5% node positive disease. The complete response rate was 60%, the local control rate was 52.5% and the loco-regional failure free survival at 5 years was 56%. The colostomy-free survival was I-"4-% and the 5-year overall survival was 4-0.67%. Haematological, gastrointestinal and skin toxicities were reviewed and the most common acute side effect experienced was grade 2[32.5%] and grade 3[4-15%] skin toxicity. Conclusion: The patient characteristics and treatment toxicities are in keeping with previous study ﬁndings. However, complete response rate and overall survival were less than expected. Although there was no statistically significant difference in overall survival between the two cohorts of patients, there was a deﬁnite trend to inferior treatment outcomes of those patients treated with continuous chemoradiation. We propose radiation dose escalation for future treatment of patients presenting with anal carcinoma at Groote Schuur Hospital.